2010
DOI: 10.1186/1743-422x-7-253
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between the Hybrid Capture II test and PCR based assay for the detection of human papillomavirus DNA in oral submucous fibrosis and oral squamous cell carcinoma

Abstract: BackgroundOral malignancy is a major global health problem. Besides the main risk factors of tobacco, smoking and alcohol, infection by human papillomavirus (HPV) and genetic alterations are likely to play an important role in these lesions. The purpose of this study was to compare the efficacy of HC-II assay and PCR for the detection of specific HPV type (HPV 16 E6) in OSMF and OSCC cases as well as find out the prevalence of the high risk HPV (HR-HPV) in these lesions.Methods and materialsFour hundred and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 25 publications
3
45
0
3
Order By: Relevance
“…[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] For the studies using a methodology similar to ours (oral brushing to collect epithelial cells instead of biopsy, combined with PCR for detection and genotyping), the prevalence reported for oral cancer cases was 31.5 26 and 32.4%. 15 Our results are in agreement with two studies conducted in Gujarat and Mumbai in West India, which reported a null prevalence of HPV in oral cancer using biopsies (in one of the studies, only HPV-16 and 18 were tested). 27,28 However, considering the fact that only two previous studies showed a null prevalence in oral cancer in India, we explored other explanations for these results.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] For the studies using a methodology similar to ours (oral brushing to collect epithelial cells instead of biopsy, combined with PCR for detection and genotyping), the prevalence reported for oral cancer cases was 31.5 26 and 32.4%. 15 Our results are in agreement with two studies conducted in Gujarat and Mumbai in West India, which reported a null prevalence of HPV in oral cancer using biopsies (in one of the studies, only HPV-16 and 18 were tested). 27,28 However, considering the fact that only two previous studies showed a null prevalence in oral cancer in India, we explored other explanations for these results.…”
Section: Discussionmentioning
confidence: 99%
“…The different HPV types are characterized by variations in the DNA sequences of L1 and divided into high-and low-risk types [15]. High-risk types include HPV- 16,18,31,32,33,35,39,45,51,52,56,58,59,66, and 68, and low-risk types are HPV-6, 11, 42, 43, and 44. The high-risk HPV (HR-HPV) types 16 and 18 are the most common etiological agents in 70% of cervical cancers globally.…”
Section: Hpv Biologymentioning
confidence: 99%
“…The primers for the PCR-based assays constitute either MY09/ MY11 or GP5+/GP6+ regions with specificity of 91.19-92.76% and sensitivity of 87.14-100% [26,35] HPV types and formalin-fixed tissues are not usable; the specificity and sensitivity are comparable to HPV DNA PCR tests [36]. p16 is a cellular correlate of increased E6 and E7 expression in HPV-positive cancers and immunohistochemical detection of p16 is an inexpensive and standard technique for clinical assessment of HPV status irrespective of the HPV type.…”
Section: Hpv Detectionmentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t in biological specimen and detected by measuring chemiluminiscence (figure 3) (Chaudhary et al, 2010;Knoepp et al, 2010). It has been proposed that it can become an effective HPV screening tool in low and middle resource countries if performed in adjunct to highly specific cytological tests.…”
Section: Page 8 Of 35mentioning
confidence: 99%